2014
DOI: 10.1155/2014/104214
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Characterisation of Anaemia in Diabetic Foot Ulceration

Abstract: Introduction. Diabetic foot ulceration (DFU) is the commonest cause of severe limb ischaemia in the western world. In diabetes mellitus, anaemia is frequently unrecognized, yet studies have shown that it is twice as common in diabetics compared with nondiabetics. We aimed to assess the incidence of anaemia and further classify the iron deficiency seen in a high-risk DFU patient group. Methods. An observational study was undertaken in a multidisciplinary diabetic foot clinic setting. All patients with DFU atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 23 publications
2
39
1
1
Order By: Relevance
“…Several studies suggest that anemia is twice as common in diabetics compared with non-diabetics [2]. Despite these facts, anemia is unrecognized in 25% of the diabetic patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that anemia is twice as common in diabetics compared with non-diabetics [2]. Despite these facts, anemia is unrecognized in 25% of the diabetic patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that anemia is twice as common in diabetics compared with non-diabetics. Despite these facts, anemia is unrecognized in 25% of patients with diabetes [18,19]. Anemia also develops earlier and is more severe in patients with diabetes than in patients with renal impairment from other causes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-angiopathy is a result of changes in the microcirculation which is caused by changes in blood viscosity and red blood cell deformability [30] . One of the variables deciding the cell deformability is the erythrocyte cytoplasmic viscosity that is basically determined by the properties and the concentration of hemoglobin in the erythrocyte [31] . Many factors were suggested as causing the frequent onset of anemia, including chronic inflammation, diabetic nephropathy, and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The transport of iron to the bone marrow is inhibited due to the scavenging of iron by macrophages and its storage in ferritin. Wright et al (2014) [31] found the prevalence of anemia in patients with severe DFU. Their explanation was due to systemic inflammation, repeated superficial, deep tissue infection, osteomyelitis, and antibiotic use which may delay healing of foot ulcer.…”
Section: Discussionmentioning
confidence: 99%